KEABSAHAN PENETAPAN KETENAGAKERJAAN DITINJAU DARI UNDANG-UNDANG NO. 2 TAHUN 2004 DAN UNDANG-UNDANG NO. 30 TAHUN 2014 - Nadeak, Nason; Fahruddin, M. Husni (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2025)
This study aims to examine the legality of labor inspection determinations issued by Labor Inspectors in resolving disputes over overtime wages, in light of Law No. 2 of 2004 on Industrial Relations Dispute Settlement and Law No. 30 of 2014 on Government Administration. The research method employed is normative legal research with a statutory approach and a conceptual approach. The findings reveal that the authority of Labor Inspectors to issue determinations or re-determinations regarding overtime wage disputes, as regulated in Minister of Manpower Regulation No. 33 of 2016 jo. Minister of Manpower Regulation No. 1 of 2020, lacks a strong legal foundation, as it contradicts the dispute settlement mechanisms stipulated in Law No. 2 of 2004. Furthermore, such actions violate the principles of good governance under Law No. 30 of 2014 and potentially prolong the resolution process of industrial relations disputes. Therefore, the provisions within the Ministerial Regulation granting authority to Labor Inspectors to issue determinations or re-determinations are legally invalid.